BERBICARA TANPA KECEMASAN DALAM PRAKTEK PUBLIC SPEAKING - Ratna Kartika Sari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Public speaking is a skill that absolutely must be mastered by everyone from various professions, including leaders. A public speaker must learn, understand, and apply the methods and techniques of pushing the right material according to the characteristics of the audience invited and the material to be delivered. The biggest obstacle faced actually comes from the public speaker himself, such as fear, fear, feelings of shame, lack of confidence, and lack of discipline. This qualitative research aims to overcome the public speaking obstacles faced by RT administrators in RW.02 Bambu Apus and to help provide solutions to overcome these obstacles. The results of the research revealed that anxiety is an obstacle that always arises when appearing to speak in public, especially if the event is attended by important people or government officials at a higher level. This anxiety eventually creates other obstacles, such as being assertive, hands feeling cold, shaking, not focusing on the material, and being at a loss for words. Practices that are carried out continuously and consistently, as well as creativity in conveying material are the keys to success in public speaking.